2011
DOI: 10.1364/ol.36.001398
|View full text |Cite
|
Sign up to set email alerts
|

Quadriwave lateral shearing interferometry in an achromatic and continuously self-imaging regime for future x-ray phase imaging

Abstract: We present in this Letter a type of quadriwave lateral shearing interferometer for x-ray phase imaging. This device is based on a phase chessboard, and we take advantage of the large spectrum of the source to produce interferograms with a propagation-invariant contrast. Such a grating has been created for hard x-ray interferometry and experimentally tested on a synchrotron beamline at Soleil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…20,[22][23][24][25][26] Moreover, the formulas for the 1-D phase grating interferometry can easily be derived from the general twodimensional theory through a dimension reduction. As is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…20,[22][23][24][25][26] Moreover, the formulas for the 1-D phase grating interferometry can easily be derived from the general twodimensional theory through a dimension reduction. As is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This is because this technique may provide highly sensitive means for imaging soft tissues and low-Z materials, hence it has many potential applications in medical imaging and material science [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. X-ray grating interferometry is usually implemented as a Talbot-Lau interferometer [4,[15][16][17], which consists of an X-ray source, a source grating G 0 , a phase grating G 1 and an imaging detector, as is schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Even though very small grating periods necessitate interferometer designs outside the near field regime, a number of studies showed that far field interferometers can work as well under the right geometric configurations. [10][11][12][13] Another motivation for smaller grating periods is the image resolution. Recently, a number of promising approaches have been developed in x-ray microscopy that utilizes gratings to extract phase contrast.…”
Section: Introductionmentioning
confidence: 99%